CONSTRUCTION OF FEMININITY IN MEDIA SPECTACLE: THE PHENOMENON OF INDONESIAN TIKTOKER CROSS GENDER PERFORMANCES - Xue, Jiang; Solihat, Ade (International Review of Humanities Studies, 2024)
In the development of the short video industry in Southeast Asia in recent years, cross gender performances by male bloggers have become a special cultural phenomenon that is rapidly emerging. It has become a new self media trend for male bloggers to imitate female images and construct femininity. This article uses media spectacle theory as a perspective to interpret the reasons for the rise, presentation methods and meaning construction of cross gender performances by Indone sian male bloggers. This article uses qualitative research methods, combining media spectacle theory and gender studies theory to research and analyze six Indonesian male bloggers. The study concluded that Indonesian male bloggers use short videos as a med ium to present cross gender performances through character visual images, scenes and words, forming a media spectacle through the interaction between video bloggers, commercial capital and the audience. This kind of gender performances brings challenges to traditional hegemonic gender temperament and attempts to cross binary gender boundaries. But It also has the problem of cultural production tending to be vulgar.